Las Efesíacas de Jenofonte de Éfeso y los Hechos Apócrifos de Pedro y Pablo: Estudio lingüístico (1) (Minerva. Revista de Filología Clásica, 2019)
It has been generally accepted until today that there are many thematic and linguistic coincidences between ancient Greek romances and Apocryphal Acts of the Apostles; it is a very dangerous affirmation without an exhaustive analysis of the texts. With this paper, whose first part is devoted to phonetics and morphology, we try to fill a gap in the study of Acta Pauli and Acta Petri. We do this from a linguistic point of view, comparing those texts with Xenophon's Έφεσιακά after Mann's work, in order to modernize it. We can see some parallelisms relating to contents, but not to language.